Impact of Competency Based Training Need Assessment on Individual Performance: A Study on Employees of Essel Mining Industries - Gayatri Panda, Ms; Sumita Mishra, Dr. (International Journal of Engineering and Technology, 2018)
With the increase in competition among different players in the mining industry, it has become an area of attention and focus for every player in the industry to streamline their employeeâ€™s competencies with the job requirement and outline the gap and design optimum strategies to bridge the gap in order to overcome the deficiencies. The present work is a lucid attempt to study the impact of competency management on identification of training need among employees of Essel Mining & Industries ltd. To achieve the set objectives a questionnaire was designed and it was distributed to a sample size of 112. The data was collected based on Purposive sampling. Correlation, Single factor ANOVA, technique was used to identify the present level and the expected level. Based on the above analysis and interpretations suggestions were given to bridge the gap and match the employeeâ€™s competencies with organizations set goals and objectives.Â